The Role of Digital Competence and Work Ethic in Improving Seafarer Performance in Indonesia - Indang Noerkajati; Edi Abdurachman; Olfebri Olfebri; Librita Arifiani; Lira Agusinta; Novita Widyaningrum (Dinasti Publisher, 2026)
Seafarers' performance has a strategic role in ensuring the safety, operational efficiency, and sustainability of the maritime industry amid the acceleration of digital transformation. The application of digital-based ship technology requires seafarers not only to master technical skills, but also to have digital competencies and a strong work ethic. This study aims to systematically examine the influence of digital competence and work ethic on seafarers' performance through the Systematic Literature Review (SLR) approach combined with bibliometric analysis. Literature searches were conducted on Scopus, ScienceDirect, SpringerLink, PubMed, and Google Scholar databases for publications for the period 2015–2025, with reference to the PRISMA guidelines. Out of the initial 1,000 articles, 20 empirical articles were obtained that met the criteria for qualitative synthesis, while bibliometric analysis was carried out using the VOSviewer software. The results of the study show that digital competence contributes significantly to improving seafarers' performance through strengthening knowledge, skills, and the ability to implement ship technology. Meanwhile, work ethic plays an important role in shaping seafarers' discipline, motivation, and professionalism, which reinforces consistency of performance in high-risk maritime work environments. The study confirms that the integration of digital competencies and work ethic is a key prerequisite for sustainable seafarer performance development, as well as providing strategic implications for shipping companies, maritime education institutions, and policymakers.